Early Complications of Endoscopic Third Ventriculostomy in Obstructive Hydrocephalus: Endoscopic Third Ventriculostomy in Obstructive Hydrocephalus - Pathan, Sanaullah; Ullah, Hameed; Bhand, Muzafar Ali; Ali, Muhammad Hamid; Aghani, Suhail Ahmed; Khimani, Vashdev (Pakistan Journal of Health Sciences, 2024)
Obstructive hydrocephalus (HCP) occurs when cerebrospinal fluid is blocked leading to the enlargement of ventricular pathways stream resulting into increase pressure within skull. Endoscopic third ventriculostomy (ETV) is considered an effective management strategy for hydrocephalus especially for third/fourth ventricle level. Objective: To study the per-operative and post-operative early complications of endoscopic third ventriculostomy in obstructive hydrocephalus patients. Methods: This prospective study was conducted at Department of Neurosurgery, Liaquat University Hospital, Hyderabad, from 1st January 2020 to 31st December 2022. One hundred and fifty patients were included. All the cases, were underwent general anesthesia and elective surgery was performed in them. The patients were followed post operatively for 7 days in context to cerebrospinal fluid (CSF) leakage, wound infection, bleeding, seizures as well as meningitis. Results: Seventy six (50.7%) were males and 74 (49.3%) were female. Mean age was 5.5 ± 2.3 years with maximum number of patients (70.7%) were under or equal the age of 5 years. Complications occurred in 18 patients (12%) out of 150 patients. Cerebrospinal fluid leakage was the most common complication occurred in 5 (3.33%) patients, wound infection was seen in 2 (1.3%) patients, meningitis developed in 3 (2%) patients, minor bleeding was seen in 3 (2%) patients, seizures developed in 4 (2.6%) patients, in hospital mortality occurred in 1 (0.66%) patient on 3rd post-operative day. Conclusions: Ventriculostomy appeared to be the better surgical approach for obstructive hydrocephaly management. Minimum numbers of associated complications were observed in present study group.